Adaptive event-triggered output-feedback stabilization for nonlinear systems with function control coefficients - Zhang, Yu; Jin, Shaoli; Li, Hui; Pan, Yue (Nonlinear Analysis: Modelling and Control, 2026)
This article presents an adaptive event-triggered control scheme for global stabilization of uncertain nonlinear systems with function control coefficients, input matching uncertainty, and unknown polynomial-function rates. A single dynamic gain observer is designed to handle these complexities, replacing the traditional dual-gain approach. An extended state observer asymptotically estimates the input matching uncertainty. An adaptive output-feedback controller, based on a time-varying threshold event-triggering mechanism, ensures closed-loop system stabilization and prevents Zeno behavior. Simulation results validate the proposed strategy